86 The emotional impact on professional healthcare interpreters of interpreting palliative care conversations for adult patients: a rapid review. (14th March 2023) - Hancox, Jennifer; McKiernan, Clare; Martin, Alice; Tomas, Jon; MacArtney, John
Abstract : Background: Professional healthcare interpreters improve patient outcomes for patients with Limited English Proficiency, both in and outside of palliative care. Healthcare professionals working within palliative care are at risk of psychological distress with exposure to often challenging conversations, but the impact on interpreters working in this setting is insufficiently explored. We aimed to synthesise existing findings into the emotional effects of conducting palliative care conversations on this core member of the healthcare team. Methods: A rapid review of five electronic databases was conducted in December 2021. Studies available in English identifying emotional effects on professional healthcare interpreters of interpreting common palliative care conversations for adult patients, were searched for inclusion. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework guided the review. Quality appraisal was performed using CASP checklists. Thematic analysis was conducted using NVivo. Quotes were utilised to illustrate themes. Results: 11 articles were included for analysis from the USA(5), Australia(3), Canada(2) and the UK(1). 8 interview-based, 2 online surveys and 1 quality improvement project. From the reviewed papers, themes were identified under three categories. (1) Emotional effects: including stress, discomfort, loneliness, guilt. (2) Factors Influencing Emotional Effects: moral conflicts and the role of the interpreter, perceived clinician communication, barriers to seeking support, relational and interpreter factors. (3) Recommendations to mitigate negative emotional effects: pre-briefing, debriefing and interpreter/provider training. Conclusion: Interpreters experience a range of emotional responses to palliative care conversations. Moral conflict resulted when expectations of the interpreter's role were unclear; when interpreting verbatim (acting as a neutral conduit) clashed with the desire to deliver information in a culturally sensitive way (acting as a cultural broker). Improving role clarity and collaborative clinician-interpreter training may alleviate negative emotional effects. Evidence limited by rapid nature of review and location/heterogeneity of studies.